MVA-Spike encoding the A subunit of dmLT safely enhances systemic and mucosal immune responses - Rambichler, Stephan; Kassub, Ronny; Carrasco-León, Rodrigo; Lämmermann, Kerstin; Feigl, Markus; Bathke, Barbara; Durand, Clémentine; Fras, Živa; Heiseke, Alexander; Riedl, André; Koppius, Andrea; Brod, Florian; et al. (Frontiers in Immunology, 2026)
IntroductionMucosal immunity provides frontline protection at respiratory, gastrointestinal, and urogenital surfaces, where secretory IgA and tissue-resident T cells such as TH17 limit colonization and early replication of pathogens. Conventional parenteral vaccines typically induce robust systemic immunity but fail to elicit strong mucosal responses. Therefore, the development of safe and effective strategies to enhance mucosal immunity remains a key priority in vaccine research.MethodsWe designed a modified vaccinia virus Ankara (MVA) construct expressing the double mutated heat-labile enterotoxin (dmLT) or only its double mutated A subunit (dmLT-A) together with Spike protein of SARS-CoV-2. C57BL/6 mice were immunized either intramuscularly or intranasally and immune responses as well as safety were monitored.ResultsHere we show that encoding the A subunit of dmLT in MVA-Spike (MVA-Spike-dmLT-A) enhances systemic and mucosal immune responses after intramuscular or intranasal immunization compared to non-adjuvanted MVA-Spike. MVA-Spike-dmLT-A elicited a multifunctional T helper response including the induction of TH17 cells in spleen and lung. This was accompanied by the efficient generation of Spike-specific antibodies in blood and lung including IgA. Histological analysis revealed the formation of organized lung-associated lymphoid structures in mice immunized with MVA-Spike-dmLT-A. Importantly, MVA encoding the holotoxin dmLT led to a massive influx of immune cells and secretion of proinflammatory mediators in the lung resulting in significant weight loss after intranasal immunization. By contrast, MVA-Spike-dmLT-A was well tolerated and did not show any signs of toxicity.ConclusionOur findings demonstrate that the A subunit of dmLT is a potent in-built adjuvant when expressed by MVA. It induces systemic and mucosal immune enhancement comparable to the full toxin mutant without any toxicity. Combining the strong immunogenic profile of MVA with the mucosal immune–modulating properties of the A subunit of dmLT represents a highly effective new vaccine platform.